2011
DOI: 10.1021/ja202869d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Properties of Nanoparticulate Intermetallic Ga–Pd Compounds

Abstract: A two-step synthesis for the preparation of single-phase and nanoparticulate GaPd and GaPd(2) by coreduction of ionic metal-precursors with LiHBEt(3) in THF without additional stabilizers is described. The coreduction leads initially to the formation of Pd nanoparticles followed by a Pd-mediated reduction of Ga(3+) on their surfaces, requiring an additional annealing step. The majority of the intermetallic particles have diameters of 3 and 7 nm for GaPd and GaPd(2), respectively, and unexpected narrow size dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
159
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 29 publications
11
159
0
2
Order By: Relevance
“…Indeed, when methane decomposes into coke, more hydrogen is produced, explaining the initial pulse responses observed in the TAP measurements. In subsequent pulses, the hydrogen production per pulse decreases, but still exceeds the amount expected based on reactions (1) and (2). During the first pulses, a rapid blockage of adjacent Pd sites occurs by coke via reactions (1) to (4).…”
Section: Initial Activity Lossmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, when methane decomposes into coke, more hydrogen is produced, explaining the initial pulse responses observed in the TAP measurements. In subsequent pulses, the hydrogen production per pulse decreases, but still exceeds the amount expected based on reactions (1) and (2). During the first pulses, a rapid blockage of adjacent Pd sites occurs by coke via reactions (1) to (4).…”
Section: Initial Activity Lossmentioning
confidence: 92%
“…[31][32][33][34][35][36] Wet incipient impregnation and incorporation of the active metals in the support appear to offer promising perspectives for implementation at a larger scale. 2,37,38 Indeed, incorporation of the active metals within the support via a one pot synthesis is an easy and reproducible route for bimetallic catalyst synthesis. For propane dehydrogenation into propene, incorporation of the active metals in a hydrotalcite-based support has already proven to yield superior catalysts when compared with wet incipient impregnation.…”
Section: Ch 3 Ch 2 Oh ⇌ Ch 3 Cho + Hmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Schaak et al reported the synthesis of a number of nanocrystalline intermetallic compounds using lowtemperature solution chemistry methods. 8−11 The use of organic stabilizers in their synthetic protocol provides limited protection against aggregation of the nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…The compounds 1 and 2 are the first examples for HumeRothery-type intermetallic molecular clusters approaching the limit for classification as "metalloid" M n R c (n = 12; c = 10; c < n). Hume-Rothery nanophases, for example, Fe 4 Al 13 , [20] PdGa, [21] and NiGa, [22] attracted attention as selective semihydrogenation catalysts of alkynes to alkenes (active site isolation concept). These findings suggest inexpensive and abundant alternatives for established but rare and precious noble metal catalysts (for example, Pt, [23] Pd, [24] Ru, [25] Rh, [26] or Au [27] ).…”
mentioning
confidence: 99%